2019
DOI: 10.15294/jllr.v1i1.35772
|View full text |Cite
|
Sign up to set email alerts
|

Law Enforcement and Legal Reform in Indonesia and Global Context: How the Law Responds to Community Development?

Abstract: Law enforcement in Indonesia has its own complexities, as law reform which has its challenges. The first edition of the Journal of Law and Legal Reform presents ten articles relating to law enforcement and law reform in various sectors. In general, this edition tries to look at various facts that occur in the community, where in a number of legal cases considered unable to respond to rapid developments in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Therefore, both the law and society must adjust to the development that occurs, so that harmony occurs between the two. This is as stated by Rosana (2013) and Utari & Arifin (2019).…”
supporting
confidence: 84%
“…Therefore, both the law and society must adjust to the development that occurs, so that harmony occurs between the two. This is as stated by Rosana (2013) and Utari & Arifin (2019).…”
supporting
confidence: 84%
“…Additionally, the corruption index is related to the credibility of the state and has an impact on the currency crisis (Ozdemir, 2008). Regulation (Reg) is an important variable in research because the law in Indonesia is often unable to keep up with community developments quickly and precisely so that the credibility of rule-makers is often questioned (Utari & Arifin, 2019). Infrastructure (Infra) was chosen because Indonesia has a low infrastructure score (WEF, 2018) although this dimension greatly affects business performance (Byrd, Lewis, & Ford, 2005;Portugal-Perez & Wilson, 2012).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Illegal funds (illicit funds) are not like the world in general, because these funds can damage the market, harm the legitimate market participants, and always do not contribute to longterm economic development and market stability where the funds are hidden. Some previous research confirmed that money laundering is a well-organized crime, neat, involving many parties, with technological sophistication and adequate skills, even in some cases, this activity involves expert actors who come from abroad (Arifin, Utari, & Subondo, 2017;Arifin, Rodiyah, & Puspita, 2019;Arifin, 2014;Utari & Arifin, 2019;Arifin & Choirunnisa, 2019;Ardianysah, Rifai'I & Rosidah, 2021).…”
Section: Introductionmentioning
confidence: 93%